2009
DOI: 10.1007/s11270-009-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, Geochemical, and Microstructural Characteristics of Road Dust on Roadsides with Different Traffic Volumes—Case Study from Finland

Abstract: The combination of magnetic, geochemical, and microstructural methods was used to characterize road dust properties in roadside soils of two sites in southern Finland: a highway (Tuusula no. 45, high traffic volume) and a local road (Mikkeli no. 13, low traffic volume). Significant differences in horizontal (κ) and vertical (χ) distribution of magnetic susceptibility were observed in the investigated roadside soils. These variations were concluded to be mostly associated to traffic volume, which is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 34 publications
3
35
0
5
Order By: Relevance
“…Besides natural factors, human activity may affect soil magnetism in many ways. Anthropogenic pollutants containing magnetic fractions, mainly derived from industry and transportation vehicles, can enhance soil magnetism in the surface layer (Blundell et al, 2009b;Bucko et al, 2010;Karimi et al, 2011;Meena et al, 2011). Cultivation may be another factor influencing soil magnetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Besides natural factors, human activity may affect soil magnetism in many ways. Anthropogenic pollutants containing magnetic fractions, mainly derived from industry and transportation vehicles, can enhance soil magnetism in the surface layer (Blundell et al, 2009b;Bucko et al, 2010;Karimi et al, 2011;Meena et al, 2011). Cultivation may be another factor influencing soil magnetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…As first observed by Hunt et al (1984) and later confirmed by Hoffman et al (1999) and Buaeko et al (2010), car emissions are also a source of technogenic magnetic particles (TMPs), which are the main carriers of heavy metals. TMPs are mainly magnetic Fe oxides and hydroxides, which presence in material can be easily detected via magnetic susceptibility measurements.…”
Section: Introductionmentioning
confidence: 82%
“…Research conducted so far has demonstrated that most car emissions are deposited in the close vicinity of roads (up to 10 m, with levels decreasing with increasing distance from the road edge (Hoffmann et al 1999, Buaeko et al 2010, Wawer et al 2015, Ojha et al, 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Результати вивчення доменного стану маг-нетиків зразків ґрунтів (Рис. 2) узгоджуються із даними наведеними у публікації [5]. Отже справді, крупнозерни-стий магнетит є основним магнітним мінералом забру-днених ґрунтів та знаходиться у межах псевдооднодо-менного-мультидоменного стану.…”
Section: а бunclassified
“…Отже справді, крупнозерни-стий магнетит є основним магнітним мінералом забру-днених ґрунтів та знаходиться у межах псевдооднодо-менного-мультидоменного стану. Крім того, спираючись на дані [5], у такому випадку ми можемо стверджувати, що концентрація міді, цинку та свинцю у забруднених ґрунтах та пилових фракціях є вищою у порівнянні із ґрунтами лісової території Трускавця.…”
Section: а бunclassified